The Healthy Currency – An Alternative to Stable Currency - Mihaela Iavorschi; Andreea Gradinaru (CES Working Papers, 2014)
In the current historical and economic context of the globalised world, sensitive to fluctuations and liable to economic crisis, we find it especially important to analyse the concept of monetary stability. The purpose of this paper is to critically analyse the concept of monetary stability, from the merchandise-currency point of view as well as regarding the fiduciary currency. Through the contributions of the Austrian economists, that underlined the mutations that occur after the inflationary processes in the allocation of resources, revenue distribution and in the evolution of entrepreneurial activities, we understand the necessity to use a healthy currency. The conclusions of the study reflect the undisputed virtues of the gold standard whose stabilizing mechanisms can only function on a free market, guaranteed by economic freedom and without the state's intervention.
Keywords: B13; E42; E52; 330; monetary stability; free market; gold standard; stable currency